Neuroprotection against beta-amyloid toxicity by the novel estrogen receptor modulator STX requires convergent signaling pathways - Lee, Hun-Joo; Bostick, Zoe; Doherty, John; Swanson, Tracy L.; Kelly, Martin J.; Quinn, Joseph F.; Gray, Nora E.; Copenhaver, Philip F. (Frontiers in Molecular Neuroscience, 2025)
IntroductionSTX is a synthetic non-steroidal estrogen receptor modulator (SERM) that can provide many of the beneficial effects of 17β-estradiol in the brain without its adverse side effects, via its selective engagement of the membrane estrogen receptor GqMER. Using both neuronal culture assays and transgenic mouse models of Alzheimer’s disease (AD), we have shown that STX protects against the deleterious effects of β-amyloid (Aβ), in part by supporting mitochondrial function and synaptic integrity. However, the specific transduction pathways by which STX induces these beneficial responses have not been previously investigated.MethodsUsing the MC65 neuroblastoma model of Aβ toxicity and primary cultures of hippocampal neurons from the 5XFAD mouse model of AD, we analyzed the involvement of different signal transduction pathways associated with STX-dependent responses in other contexts. We used pharmacological methods to test the role of key pathway components in assays of cell viability, neuronal morphology, quantitative immunoblots to analyze pathway engagement, and modulation of the mitochondrial permeability transition pore.ResultsWe found that the neuroprotective effects of STX against Aβ toxicity required engagement of the PI3K/Akt/GSK3β pathway. Using well-characterized inhibitors of specific isoforms of the p110 catalytic domain of PI3K, we then showed that this response was predominantly mediated via engagement of the P110δ isoform, with a more modest contribution by P110β. In contrast, targeting the PLC/PKC/PKA pathway (which plays a prominent role in hypothalamic neurons) had a relatively modest effect on the neuroprotective responses induced by STX, while targeting ERK/MAPK signaling had no significant effect.DiscussionIn combination with our previous studies, these results indicate that engagement of GqMER by STX promotes neuroprotective responses via convergent signaling pathways that mitigate the effects of Aβ toxicity on mitochondrial function, synaptic integrity, and neuronal calcium (Ca2+) homeostasis. They also provide the framework for testing the mechanisms of STX neuroprotection in vivo, using mouse AD models. Since STX has been shown to provide many of the beneficial effects of 17β-estradiol in the brain without its adverse side effects (including feminizing effects in males), these results support the hypothesis that STX might have therapeutic potential in patients at risk of AD.